Microbial diversity regulates ecosystem multifunctionality during natural secondary succession. Issue 12 (18th September 2021) - Shi, Xiuzhen; Wang, Jianqing; Lucas‐Borja, Manuel Esteban; Wang, Zhenyu; Li, Xue; Huang, Zhiqun
Abstract: Natural forest succession after disturbances is one of the most important restoration strategies. However, the responses of ecosystem multifunctionality during natural forest succession remains poorly understood in forest ecosystem. Here we evaluated how the ecosystem multifunctionality including nutrient cycling, carbon stocks, water regulation, decomposition, wood production and symbiosis develops using a chronosequence, and identified the key factors contributing to the variations in the ecosystem multifunctionality during natural forest succession. We provide evidence that the ecosystem multifunctionality gradually increased along with succession stages. The individual functions of carbon stocks and water regulation also exhibited increasing patterns with stand development. The microbial diversity were more principal factors than plant diversity and soil properties for the explanation of changes in the ecosystem multifunctionality. The regression analysis showed that the diversity of bacteria, general fungi, actinomycetes, nematodes, G + bacteria and G − bacteria significantly and positively associated with ecosystem multifunctionality. Soil nematodes exhibited significantly positive correlation with most of the individual functions. Synthesis and applications . Taken together, our results demonstrate that natural forest restoration plays a key role in promoting ecosystem multifunctionality, and emphasize the importance of soil microbial diversity for the maintenance of ecosystem functions and health. Abstract : Taken together, our results demonstrate that natural forest restoration plays a key role in promoting ecosystem multifunctionality, and emphasize the importance of soil microbial diversity for the maintenance of ecosystem functions and health.